2006
DOI: 10.1148/radiol.2401051161
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of Stress Perfusion and Delayed-Enhancement MR Imaging in Patients with Coronary Artery Disease

Abstract: Stress first-pass perfusion MR imaging followed by delayed-enhancement imaging is an accurate method to depict significant coronary stenosis in patients suspected of having or known to have CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
2

Year Published

2008
2008
2011
2011

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(52 citation statements)
references
References 22 publications
2
48
0
2
Order By: Relevance
“…As a matter of fact, a recent populationbased study in Sweden showed that 19.8% of randomly selected 70-year-old subjects had subclinical myocardial infarct reflected as focal area of LGE [27]. Several studies have demonstrated that combining LGE MRI with stress-rest perfusion MRI can improve the sensitivity of MRI for obstructive CAD without deteriorating the specificity when only obvious myocardial infarction (i.e., LGE consistent with a coronary distribution) were considered [28,29]. However, correlating the presence of LGE with flow-limiting obstructive CAD can be inappropriate since microinfarcts may occur without coronary artery narrowing as a result of plaque rupture/ ulceration and subsequent washout of the lipid pool with or without additional thrombus formation into the microcirculation [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…As a matter of fact, a recent populationbased study in Sweden showed that 19.8% of randomly selected 70-year-old subjects had subclinical myocardial infarct reflected as focal area of LGE [27]. Several studies have demonstrated that combining LGE MRI with stress-rest perfusion MRI can improve the sensitivity of MRI for obstructive CAD without deteriorating the specificity when only obvious myocardial infarction (i.e., LGE consistent with a coronary distribution) were considered [28,29]. However, correlating the presence of LGE with flow-limiting obstructive CAD can be inappropriate since microinfarcts may occur without coronary artery narrowing as a result of plaque rupture/ ulceration and subsequent washout of the lipid pool with or without additional thrombus formation into the microcirculation [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…50%) or in patients with a lower likelihood of disease or risk factors. Single-center (32,35,37,41) and multicenter (42) studies have shown FIGURE 3. MBF can increase 3-to 4-fold during submaximal increase in cardiac workload to match increased myocardial oxygen demand.…”
Section: Mbf Measurement: Recent Advances Cmrmentioning
confidence: 99%
“…But there is also a dilemma for cardiologists and their patients with known CAD, after multiple coronary interventions and finally coronary bypass grafting, who after a symptom-free period of three years develop angina again. Neither established diagnostic methods such as 12-lead ECG, [15][16][17][18][19][20]. Transient myocardial ischaemia, however, causes well-recognizable changes in a variety of MCG parameters, first described by Cohen and Kaufman in 1975 [21].…”
Section: Coronary Artery Diseasementioning
confidence: 99%